Contribution to Malawi's National Agricultural Extension and Advisory Services Strategy, launched in 2020 to guide investments - CGIAR Research Program on Policies, Institutions, and Markets (2020)
In December 2020, the Government of Malawi launched the National Agricultural Extension and Advisory Services Strategy (NAEASS), a document aimed at guiding the country’s agricultural extension investments in the next five years. This strategy is the outcome of over two years of stakeholder consultations and review in which IFPRI was heavily involved. PIM-supported IFPRI research is cited in several documents pertaining to the development of the policy and in draft versions of the NAEASS itself.